Divergency of Emotion in the Perspective of Neuro-sciences and Islam - Puspa Handayani; M. Ansya Al-Asrori; Nur Halimah; Malikhatun Natiqoh; Wildan Alim (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Since the emergence of the symptoms neuroscience in our body the center is in the brain, one of them is emotion. Emotions are intense feelings directed at someone or something, there are differences in studying emotions according to Islamic religion and neuroscience. In neuroscience emotions lie within the limbic system of the brain, whereas in Islamic religion emotions lie in the heart (Qolb). Therefore there are significant differences regarding the emergence of emotions in the neuroscience and religion of Islam, for that we try to correlate with the perspective of the neuroscience and Islam so as to produce an interconnected perspective between the two.